Synthesis, characterization and antimicrobial evaluation of silver nanoparticles embedded alkyd resin derived from pine seed oil - Magaji, A; Musa, H; A Sheshe, F; I Alhassan, S (International Journal of Advanced Chemistry, 2021)
Silver nanoparticles were synthesized by reducing 0.1mmol silver Nitrate salt with 5ml of neem leaf extract, in an environmental friendly process. The nanoparticles were tested to have strong zones of inhibition on the antibacterial and antifungal isolates; E. Coli, staphylococcus aureus, Aspergillus fumigatus, and mucor species used. UV-visible spectrophotometric analysis was carried out on both the silver nitrate salt and silver nanoparticles, which show bathochromic shift from 221nm (AgNO3) to 440nm (AgNPs). Pine seed oil was condensed to alkyd resin via two step reactions; alcoholysis and esterification reactions respectively, and was characterized by FTIR, acid value and viscometric measurement. Antimicrobial evaluation was carried out on the pine seed oil with its alkyd resin. Pine alkyd resin was used in the formulation of paints with percentage Pigment Volume Concentrations (%PVC) 4 and 5% respectively, and is classified as automotive clearcoat. Chemical resistance, scratch resistance, light fastness, and drying schedule tests were conducted on the paints and are found to exhibit good properties which are similar to commercial paints. Antimicrobial evaluation of the paints incorporated with silver nanoparticles revealed more inhibition zones than those without silver nanoparticles.Â Â